2016
DOI: 10.1038/srep34711
|View full text |Cite
|
Sign up to set email alerts
|

Scaffold Hopping Toward Agomelatine: Novel 3, 4-Dihydroisoquinoline Compounds as Potential Antidepressant Agents

Abstract: A scaffold-hopping strategy toward Agomelatine based on in silico screening and knowledge analysis was employed to design novel antidepressant agents. A series of 3, 4-dihydroisoquinoline compounds were selected for chemical synthesis and biological assessment. Three compounds (6a-1, 6a-2, 6a-9) demonstrated protective effects on corticosterone-induced lesion of PC12 cells. Compound 6a-1 also displayed low inhibitory effects on the growth of HEK293 and L02 normal cells and it was further evaluated for its pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Although widely investigated in in vivo conditions 3133 , the in vitro effects of fluoxetine on Bdnf mRNA expression have been reported in only a few studies. All showed that fluoxetine can activate Bdnf expression, in control conditions, as well as in stressful environments, such as under toxic conditions induced by B27 deprivation in primary rat hippocampal cultures 34 or in corticosterone-exposed PC12 cells 35 . We further confirmed and complemented those data showing that fluoxetine induces Bdnf mRNA expression and also activates immediate early gene expression, such as Egr1 and Cfos , and stimulates TrkB phosphorylation in C57Bl/6J primary cortical cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Although widely investigated in in vivo conditions 3133 , the in vitro effects of fluoxetine on Bdnf mRNA expression have been reported in only a few studies. All showed that fluoxetine can activate Bdnf expression, in control conditions, as well as in stressful environments, such as under toxic conditions induced by B27 deprivation in primary rat hippocampal cultures 34 or in corticosterone-exposed PC12 cells 35 . We further confirmed and complemented those data showing that fluoxetine induces Bdnf mRNA expression and also activates immediate early gene expression, such as Egr1 and Cfos , and stimulates TrkB phosphorylation in C57Bl/6J primary cortical cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies [3,[24][25][26] treated with FLU for time periods ranging from 1 day to 2 days, while we medicated with FLU for longer periods up to 3 days. This prolonged period found treatment with FLU has an opposite effects on the regulation of cellular neuroplasticity and microtubule plasticity at 1 day than at 3 days.…”
Section: Effects Of Treatment With Flu On Cellular Neuroplasticity Anmentioning
confidence: 99%
“…The growth state of cells or cell viability played an important role in this phenomenon. Almost all of previous studies [3,[24][25][26] regard treated with drugs from 1 day to 2 days as treatment models of antidepressants, during which the cells are in the growth phase or stable phase. The cells maintain high cell viability, which is consistent with the results of this study.…”
Section: Effects Of Treatment With Flu On Cellular Neuroplasticity Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinolines is an important class of well-known heterocyclic scaffolds; they are embedded in many biological systems and have interesting applications in agriculture, materials, chemical industry, and medicine, for instance, as antimalarial (Figure , quinine), , anticancer (Figure , camptothecin), antibacterial, , insecticide (Figure , quinclorac), and so forth. Consequently, various methods of synthesis of quinolines have been reported. Among them, the transition-metal-catalyzed C–H bond or N–H bond activation approaches have provided numerous strategies for the synthesis of quinoline. …”
Section: Introductionmentioning
confidence: 99%